Analysis of changes in stride length, time, and electromyography finding depending on athletic crouch start method - Lee, K.; Hong, W.; Kim, E. G. (Korean Journal of Sport Biomechanics, 2017)
Objective: The purpose of this study was to compare and analyze the kinematic variables and electromyography (EMG) findings that change with varying characteristics of crouch start and feedback provision, and to provide the fundamental data for record improvement in 400 mH. Method: Four short-distance runners participated in the experiment. The analyzed variables were elapsed time per interval, stride length, and muscle activities in three lower limb muscles. These variables were analyzed by using Kwon3d XP and Noraxon Myoresearch. The participants were subjected to three conditions, including two conditions that relate to the thrusting foot on the rear block and another condition pertinent to feedback provision. Results: In terms of a one-step interval, the elapsed time in condition A was longer than that in condition B, and the one after the feedback was the longest. The stride length of a one-step interval was the longest in condition A. The stride length of a two-step interval was the shortest in condition A. The muscle activity during a one-step interval showed differences in vastus medialis and medial gastrocnemius, with condition A being the highest. Conclusion: When the non-dominant left foot was located at the back, negative results were observed in terms of elapsed time and stride length. Moreover, an imbalance in muscle activity was observed between the left and right feet when the left foot was placed at the back. As a result, significant differences in elapsed time, stride length, and muscle activity were observed depending on the foot placed on the rear block. In conclusion, we identified the characteristics of crouch start in 400 mH, and a specialized program must be suggested.